The impact of perceived risk of online takeout packaging and the moderating role of educational level - Guo, Meiwen; Wu, Liang; Tan, Cheng Ling; Cheah, Jun Hwa; Abdul Aziz, Yuhanis; Peng, Jianping; Chiu, Chun Hung; Ren, Rongwei (Springer Nature, 2023)
With the rapid development of e-commerce and the impact of COVID-19, online takeout hasBbecome the first choice of more and more consumers. Previous research has indicated that food packaging is of great significance to marketing performance, yet very little is known about the mechanisms through which food packaging pollution risk affects online takeout consumption. This study proposes an expanded model of the Theory of Planned Behavior (TPB) by incorporating the Concept of Perceived Risk (CPR) to analyze the mechanism of consumers’ packaging pollution risk perception (PPRP) on their purchasing intention toward online takeout. Online survey was performed to collect data from 336 valid respondents in China, which was analyzed using structural equation modeling. The research findings verify the effectiveness of the TPB in the context of Chinese online takeout. Notably, the PPRP of online takeout was found to have a significant negative impact on consumers’ attitudes, subjective norms, and perceived behavioral control (PBC). It was also confirmed that consumers’ attitudes, subjective norms, and PBC regarding online takeout partially mediate the negative relationship between PPRP and purchase intention. In addition, the findings corroborate the granular nuances among three groups concerning consumers’ education level. The results do not only provide suggestions to the online takeout industry but also contribute theoretical value and practical significance for the improvement of sustainable food consumption.